A non-linear masonry infill macro-model to represent the global behaviour of buildings under cyclic loading - Rodrigues, H.
The presence of masonry infill walls in RC buildings is very common. However, and even today, in the design of new buildings and in the assessment of existing ones, these infill walls are usually considered as non-structural elements and their influence in the structural response is generally ignored. For horizontal loading, infill panels can drastically modify the response, attracting forces to parts of the structure that have not been designed to resist them. This paper presents an improved non-linear numerical simulation model for the influence of the masonry infill walls in the seismic behavior of structure. The model is implemented in the PORANL program. After the implementation and calibration of the proposed masonry model, a series of non-linear dynamic analyses of a building representative of Modern Architecture in Europe were carried out. The main objective was to investigate the behavior of this type of building, and any weakness under seismic loading. The building geometry and the dimensions of the RC elements and infill walls were set in the original project, and confirmed in the technical visits. The building under study has nine storeys and the structure is mainly composed of 12 plane frames oriented in the transversal direction. The building was analyzed with a simplified plane model, for each direction, and the existing infill panels were looked at in accordance with their dimensions and location. The earthquake action adopted in this study was simulated through three series of artificially generated earthquakes, for a medium/high seismic risk scenario in Europe. © 2008 Springer Science+Business Media, B.V.